Morbid obesity in pregnant women - Van de Velde, Marc (Array, 2009)
A thorough understanding of physiology, pathofysiology, associated conditions, their complications and the implications for analgesia and anaesthesia, should place the anaesthesiologist in a better position to take care of these patients. Neuraxial blockade with an indwelling catheter is the prefered method for labor analgesia in obese or morbidly obese patients. An early placement in labor is necessary to give adequate analgesia and to avoid general anesthesia in case of emergency Cesarean section.